Peran metode bercerita terhadap perkembangan bahasa anak usia dini - Salsabila, Naisa Assyfa (Maliki Interdisciplinary Journal, 2026)
Language development is an important element in children’s growth at an early age, because it is the basis of their ability to communicate, think, socialize and be emotional. One way of learning that is considered beneficial in encouraging the language development of young children is the storytelling method. This article aims to evaluate in depth the role of storytelling in early childhood language development through a literature study approach enriched by analysis of concepts and data from various previous studies. The storytelling method is defined as the activity of conveying stories verbally, either with or without the aid of tools, which is designed to attract children’s attention and invite them to participate actively in the learning process. Research shows that the storytelling method makes an important contribution to increasing children’s vocabulary, speaking ability, listening ability, sentence structure and courage to express opinions. Apart from that, the storytelling method also functions to develop imagination, interest in reading, and moral values that support overall language development. The discussion in this article confirms that the effectiveness of the storytelling method is influenced by several elements, including the teacher’s ability to tell stories, selecting stories that are appropriate to the child’s age and stage of development, and the use of interesting supporting media. Thus, it can be concluded that the storytelling method is an appropriate and effective learning strategy for optimizing children’s language development at an early age. It is hoped that this article can be a reference for educators, researchers and early childhood education practitioners in creating innovative and meaningful language learning.